ANGELIKA NEUWIRTH: KAJIAN INTERTEKSTUALITAS DALAM QS. AL-RAḤMĀN DAN MAZMUR 136 - Rahman, Zayad Abd. (STAIN Kediri, 2015)
Angelika Neuwirth is a typical Western scientist who contributed to the reviews of the Qur’an through a literary approach. Neuwirth builds her analysis on letters as a whole. In a further development, Neuwirth suggested the use of letters not only in literary approaches, but also in historical ones. For her, a letter is a small unit that stores a communication process from birth; it is also an integral unit that the editor guarantees as a literary text. She understands the Qur’an as a living scripture that reacts to other traditions during its emergence. With the study of intertextuality, the Bible’s influence on the Qur’an is not considered a plagiarism, rather a uniqueness and effectiveness of the Qur’anic messages.Keywords: Studi al-Qur’an, Intertekstualitas, Literatur.